Birgittinerna och deras bilder En studie av bild, rum och betraktare i Vadstena klosterkyrka omkring år 1500 - Sandgren, Eva (Kriterium, 2021)
This study investigates the pictorial world of the medieval Vadstena Abbey church. The interior of the church was filled with altars and images that had the three separated groups of viewers in mind: the 60 nuns, the 25 conventual brothers and the numerous pilgrims coming to visit the shrine of Saint Birgitta. The pilgrims faced a pictorial message where the role of saint Birgitta was emphasized, but still one among all the other saints. The images directed to the nuns and the brothers accentuated the role of the Virgin Mary as the exemplarily follower of Christ. Furthermore, all the church interior was furnished to enhance the position of the nuns, i.e. that this monastic foundation was made primarily for women.